인공 산성광산배수의 pH변화에 의한 중금속 제거 및 침전 특성 연구 - 이민현(Min Hyeon Lee); 김영훈(Young Hun Kim); 김정진(Jeong Jin Kim) (자원환경지질, 2019)
In this study, heavy metal removal and precipitation characteristics with pH change were studied for artificial acid mine drainage. Artificial acid mine drainage was prepared using sulfates of iron, aluminum, copper, zinc, manganese which contained in acid mine drainage from abandoned mines. The single and mixed five heavy metal samples of Fe, Al, Cu, Zn, and Mn were prepared at initial concentrations of 30 and 70 mg/L. Fe and Al were mostly removed at pH 4.0 and 5.0, respectively, and other heavy metals gradually decreased with increasing pH. Concentration changes with increasing pH show generally similar trend for single and mixed heavy metal samples. The effect of removing heavy metals from aqueous solutions is not related to the initial concentration and depends on the pH change. XRD were used for mineral identification of precipitates and crystallinity of the mineral tended to increase with increasing pH. The precipitates that produced by decreasing the concentration of heavy metals in the aqueous solution composed of Fe-goethite(FeOOH), Al-basaluminite(Al4(SO4)(OH)10·4H2O), Cu-connellite(Cu19(OH)32(SO4)Cl4·3H2O) and tenorite(CuO), Zn-zincite(ZnO), and Mn-hausmannite(Mn3O4). 본 연구에서는 pH 변화에 따른 인공 산성광산배수로부터 중금속 제거와 침전물 생성에 대한 연구를 수행하였다. 인공 산성광산배수는 폐광산에서 유출되는 산성광산배수에 다량 포함된 Fe, Al, Cu, Zn, Mn의 황산염을 이용하여 제조하였다. 실험은 5가지의 중금속에 대하여 초기 농도 30과 70 mg/L의 단일 및 혼합 시료를 이용하여 수행하였다. Fe와 Al은 각각 pH 4.0과 5.0에서 대부분 제거되었으며 그 외 중금속은 pH가 증가함에 따라 서서히 감소하였다. 단일 및 혼합 중금속 시료에 대한 pH 증가에 따른 농도 변화는 대체로 유사한 경향을 나타낸다. 수용액으로부터 중금속 제거 효과는 초기 농도와 관계없이 유사한 경향을 나타내고 pH 변화에 따라 확연한 차이를 나타낸다. X-선회절분석을 이용하여 침전물에 대한 광물 감정을 수행하였으며 pH가 증가함에 따라 결정도가 증가하는 경향을 나타낸다. 수용액 내에 중금속 농도가 감소하면서 생성되는 침전물은 Fe-침철석(FeOOH), Al-배사알루미나이트(Al4(SO4)(OH)10·4H2O), Cu-코넬라이트Cu19(OH)32(SO4)Cl4·3H2O)와 테놀라이트(tenorite: CuO), Zn-진사이트(ZnO), Mn-하우스마나이트(Mn3O4)이다.